Impact of remission and low disease activity on health-related quality of life in patients with systemic lupus erythematosus. (18th March 2022) - Emamikia, Sharzad; Oon, Shereen; Gomez, Alvaro; Lindblom, Julius; Borg, Alexander; Enman, Yvonne; Morand, Eric; Grannas, David; van Vollenhoven, Ronald F; Nikpour, Mandana; Parodis, Ioannis
Abstract: Objectives: To investigate the impact of remission and lupus low disease activity state (LLDAS) on health-related quality of life (HRQoL) in systemic lupus erythematosus. Methods: Short-Form 36 (SF-36), three-level EQ-5D (EQ-5D-3L) and Functional Assessment of Chronic Illness Therapy (FACIT)-Fatigue data from the BLISS-52 (NCT00424476) and BLISS-76 (NCT00410384) trials were used. Duration in remission/LLDAS required to reach a HRQoL benefit ≥ minimal clinically important differences (MCIDs) during and post-treatment was determined using quantile regression and generalized estimating equations. Results: Patients ( n  = 1684) were assessed every fourth week (15 visits). Four cumulative (β = 0.60) or four consecutive (β = 0.66) visits in remission were required to achieve a benefit ≥MCID in SF-36 physical component summary (PCS) scores, and six cumulative (β = 0.44) or five consecutive (β = 0.49) for a benefit ≥MCID in mental component summary (MCS) scores. Eight cumulative (β = 0.30 for both) or eight consecutive (β = 0.32 for both) visits in LLDAS were required for a benefit in PCS/MCS ≥MCID, respectively. For EQ-5D-3L index scores ≥MCID, six cumulative (β = 0.007) or five consecutive (β = 0.008) visits in remission were required, and eight cumulative (β = 0.005) or six consecutive (β = 0.006) visits in LLDAS. For FACIT-Fatigue scores ≥MCID, 12 cumulative (β = 0.34) or 10 consecutive (β = 0.39) visits in remission were required, and 17 cumulative (β = 0.24) or 16 consecutive (β = 0.25) visits in LLDAS. Conclusion: Remission and LLDAS contribute to a HRQoL benefit in a time-dependent manner. Shorter time in remission than in LLDAS was required for a clinically important benefit in HRQoL, and longer time in remission for a benefit in mental compared with physical HRQoL aspects. When remission/LLDAS was sustained, the same benefit was achieved in a shorter time.